Research 2.0 (Web 2.0 and Market Research) - Raman, Venkatesh (Journal of Contemporary Research in Management (JCRM), 2013)
Today, Web 2.0 is one of the biggest buzzwords in small, medium and large businesses. It is a term used to describe a new phase of how web is being used. Web 2.0 is the term given to describe a second generation of the World Wide Web that is focused on the ability for people to collaborate and share information online. Always the market research industry makes every effort to use the latest technology available in the market place to improve all aspects of survey design starting from data collection to analysis. But, Web 2.0 is very new to the researchers because it has entered the market research industry very recently.In today’s competitive business world, many MR companies are evaluating the benefits of Web 2.0 and its usefulness in the qualitative market research methods. Thus, the market research industry is likely to undergo key changes and Web 2.0 acts as a catalyst for changes that in turn provide cost effective, quick turn around and new breed of insights comparatively far better than traditional qualitative research methodologies like focus groups and in-depth interviews. It symbolizes the transformation of market research process that needs to be carried out in the future. This research paper highlights growing importance of Web 2.0 in the Market Research industry.